If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(18 + -6y) + -3y = -24 (18 * 2 + -6y * 2) + -3y = -24 (36 + -12y) + -3y = -24 Combine like terms: -12y + -3y = -15y 36 + -15y = -24 Solving 36 + -15y = -24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -15y = -24 + -36 Combine like terms: 36 + -36 = 0 0 + -15y = -24 + -36 -15y = -24 + -36 Combine like terms: -24 + -36 = -60 -15y = -60 Divide each side by '-15'. y = 4 Simplifying y = 4
| 5n+8=-(2-6n)+8 | | 3xsquared=6-9x | | 8x+12+9(2x-4)= | | 5z-0.6=6z | | -3=a(3-0)-4 | | -3u-1/3u=1/4-7/3 | | (8n-1)+(4n+5)= | | 7y(4y-2)= | | -4ac-5b= | | 2lnx-6=12 | | 3x-20x-7=0 | | x-9+x+5x=180 | | 3=a(3-0)-4 | | -2(7x-4)+6(5x+1)= | | 7x-1-9x+5= | | 4(6x-4)+5(15-3x)-4(2x+3)=-2 | | (x+3)+2x+x=23 | | 3x*3x*3x+4=31 | | 4b+-2a-c= | | 7x-1+9x+5= | | 2j-3=47 | | -18z+6=27z-20 | | y=x^2-10x+106 | | 1+3(m-8)=7-5(6m+6) | | 4+r=6r-3-6r | | 2/5(1-5)x=1/2(4x+3) | | x+1+x+2=180 | | 51-2(11y-12y)= | | f/2=f | | 7z-6=8z-4 | | 3(k-8)=5k | | x+y^2-6y+14=0 |